Gambaran Risiko Post-Traumatic Stress Disorder (PTSD) pada Penyintas COVID-19 di Rumah Sakit Universitas Andalas - Wahyuni, Sri; Widya Murni, Arina; Indra, Beni; Gusya Liza, Rini; Koerniati, Isnindiah; Sauma, Eldi (UI Scholars Hub, 2023)
Introduction. The COVID-19 pandemic has a negative impact on life where sufferers can experience emotional problems such as despair, deep sadness, helplessness, anxiety, and depressive symptoms. Especially in hospitalized COVID-19 survivors, there are sequelae in the form of anxiety, depression, and Post-traumatic Stress Disorder (PTSD). PTSD experienced by COVID-19 survivors will affect the patient’s quality of life in the future. This study aimed to assess the risk of PTSD in COVID-19 survivors who had been hospitalized at Andalas University Hospital. Methods. A cross-sectional descriptive study was conducted among COVID-19 survivors aged ≥15 years who had been hospitalized at Andalas University Hospital. Samples were selected by using total sampling method with inclusion criteria included experiencing mild, severe, or critical clinical symptoms during COVID-19 infection, being discharged from Andalas University Hospital for six months or more, and willing to participate in the study by signing an informed consent. Samples who have met the inclusion criteria completed the Bahasa Indonesia version of PCL-5 (PTSD Checklist for DSM-5) questionnaire which has been tested for its validity and reliability. Respondents were categorized as having PTSD risk if the questionnaire results showed a score of ≥23. The collected data were subsequently analyzed using univariate analysis. Results. A total of 75 respondents were included in the study, of which 9.3% (7) were found to be potentially or at risk of PTSD. The group of respondents who were at risk of PTSD was mostly comprised of females, and all of them experienced the four PTSD symptoms (intrusion/re-experiencing, avoidance, negative alterations in cognition and mood, and hyperarousal). The most common trigger that causes PTSD among respondents was the experience of a previous life-threatening traumatic event (71.43%). In addition, the most frequent clinical symptoms of COVID-19 in the PTSD risk group were severe clinical symptoms (71.43%). Conclusions. COVID-19 survivors who have the potential to experience PTSD are predominantly female survivors with severe clinical symptoms, experiencing all four PTSD symptoms, and having a traumatic life-threatening experience during COVID-19 hospitalization. Keywords: COVID-19 survivors, hospitalization, risk of PTSD